Disparition ou conservation des sources et abandon de l’acte écrit : quelques observations sur les actes de Jumièges - Mathieu Arnoux (Tabularia)
The documentary gap of the years 911-990 is one of the main obstacles to our knowledge of the origins of the Duchy of Normandy. It is necessary, to give their full meaning to the rare sources subsisting from that period, to question the signification of this interruption and the modalities of a return to the utilisation of written acts at the end of the century. The collection of charters of Jumièges, where at least one charter from the 10th c. subsists in original form, represents a good observation point of the use of written charters in the 10th and 11th centuries. This paper is particularly engaged in the study of the treatment to which were subjected the Carolingian charters of the Abbey, which were copied and produced in court during the 11th century. Examination of these deeds suggests that, in spite of the cessation of the production of written dispositive charters, the religious communities of the duchy never stopped copying and using the monumentae of their early history. This continuity in the preservation of written work was one of the means of their survival.